2016
DOI: 10.1007/s12310-016-9176-1
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Social, Emotional, and Behavioral Problems at Kindergarten Entry: The Utility of Two Teacher Rating Scales

Abstract: We examined (a) the utility of teacher ratings on the Strengths and Difficulties ) and BASC-2 Behavioral and Emotional Screening System (BESS; Kamphaus and Reynolds in Behavior assessment system for children-second edition: behavioral and emotional screening system. Pearson, Bloomington, 2007), completed at kindergarten entry, in identifying risk status as defined by important criterion variables (teacher ratings of impairment, daily behavioral performance, and quarterly grades in kindergarten and first grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…Similarly, in a larger elementary school sample ( N = 496), total scores had a sensitivity of 68.4% and specificity of 77.1% in identifying students referred to the office one or more times by midyear (King et al, 2012). A study examining predictive validity with kindergarten students ( N = 248) found that total scores had moderate to high utility (AUCs = 0.84 to 0.90) in predicting daily student behavior across the year, grades in kindergarten and 1st grade, and impairment (Owens et al, 2016), with positive predictive values ranging from 0.32 to 0.71 across outcomes. This study directly compared the SDQ to the BASC‐2‐BESS and found them both to be significant predictors of all outcomes, and both demonstrated incremental predictive validity beyond the prediction of kindergarten‐entry literacy scores.…”
Section: Basc‐2‐bessmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in a larger elementary school sample ( N = 496), total scores had a sensitivity of 68.4% and specificity of 77.1% in identifying students referred to the office one or more times by midyear (King et al, 2012). A study examining predictive validity with kindergarten students ( N = 248) found that total scores had moderate to high utility (AUCs = 0.84 to 0.90) in predicting daily student behavior across the year, grades in kindergarten and 1st grade, and impairment (Owens et al, 2016), with positive predictive values ranging from 0.32 to 0.71 across outcomes. This study directly compared the SDQ to the BASC‐2‐BESS and found them both to be significant predictors of all outcomes, and both demonstrated incremental predictive validity beyond the prediction of kindergarten‐entry literacy scores.…”
Section: Basc‐2‐bessmentioning
confidence: 99%
“…The teacher‐report SDQ has been shown to have predictive validity for school‐related outcomes. For example, in a sample of kindergarten children ( N = 248), the teacher‐report SDQ total score had moderate to high utility (area under the curve (AUCs) = 0.78–0.93) in predicting daily student behavior across the year, grades in kindergarten and 1st grade, and impairment (Owens et al, 2016), with positive predictive values ranging from 0.40 to 0.71. This study did not assess the predictive utility of the impact supplement scores (i.e., impairment items).…”
Section: Sdqmentioning
confidence: 99%
“…This measure was completed prior to the start of the DRC intervention, monthly during intervention, and in the spring. The teacher version of this measure has acceptable internal reliability, high test-retest correlation, and predictive utility in identifying problems in elementary school students (Goodman, 2001;Owens et al, 2016). SDQ scores are used in Aim 4.…”
Section: Strengths and Difficulties Questionnairementioning
confidence: 99%
“…Students were eligible to participate if they demonstrated at-risk or elevated levels of problems on the hyperactivity/inattention subscale, the conduct and behavior problems subscale, or the total score of the teacher-rated Strengths and Difficulty Questionnaire (SDQ; Goodman, Ford, T., Simmons, H., Gatward, R., & Meltzer, 2000). These subscales were chosen based on brevity, public availability, and moderate to strong predictive validity (AUCs > 0.75) of other indicators of school impairment (e.g., in class behavior, grades; Owens, Holdaway et al, 2016). Teachers were instructed not to refer students with previously identified intellectual disabilities, severe autism spectrum disorders, or active psychotic features.…”
Section: Participantsmentioning
confidence: 99%